2022
DOI: 10.3390/pharmaceutics14071322
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stem Cells versus Omega n − 3 Polyunsaturated Fatty Acids on Gentamicin-Induced Cardiac Degeneration

Abstract: This study compared the cardioprotective action of mesenchymal stem cells (MSCs) and PUFAs in a rat model of gentamicin (GM)-induced cardiac degeneration. Male Wistar albino rats were randomized into four groups of eight rats each: group I (control group), group II (gentamicin-treated rats receiving gentamicin intraperitoneally (IP) at dose of 100 mg/kg/day for 10 consecutive days), group III (gentamicin and PUFA group receiving gentamicin IP at dose of 100 mg/kg/day for 10 consecutive days followed by PUFAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
1
2
0
Order By: Relevance
“…PCNA is considered an indicator for spermatogenic cell proliferation, DNA replication, and its affection means spermatogenesis arrest. Our finding coincides with that of Meligy et al [56], who reported that gentamicin administration significantly reduced the PCNA immune positive cardiac cells in gentamicin-induced cardiac degeneration in comparison to control group. This can be explained by the accumulation of ROS, which has been suggested to induce DNA fragmentation [57].…”
Section: Discussionsupporting
confidence: 92%
“…PCNA is considered an indicator for spermatogenic cell proliferation, DNA replication, and its affection means spermatogenesis arrest. Our finding coincides with that of Meligy et al [56], who reported that gentamicin administration significantly reduced the PCNA immune positive cardiac cells in gentamicin-induced cardiac degeneration in comparison to control group. This can be explained by the accumulation of ROS, which has been suggested to induce DNA fragmentation [57].…”
Section: Discussionsupporting
confidence: 92%
“…Then, staining with toluidine blue was done after being cut into semithin sections (0.5–1‐m‐thick). Ultrathin sections (50–80 nm) were cut from a few semithin sections, contrasted with uranyl acetate, and then examined by an electron microscope (JEOL, JEM‐100CXII Akishima) in Assiut University's Electron Microscope Unit 33 …”
Section: Methodsmentioning
confidence: 99%
“…Ultrathin sections (50-80 nm) were cut from a few semithin sections, contrasted with uranyl acetate, and then examined by an electron microscope (JEOL, JEM-100CXII Akishima) in Assiut University's Electron Microscope Unit. 33 2.6.3 | Immunohistochemical staining for nestin, caspase, claudin, and GFAP Glass slides that had paraffin sections that were positively charged were completely deparaffinized in xylene and rehydrated in ethanol of progressively lower strengths. After that, immunostaining (Thermo Fisher Scientific Co.) was done using a modified avidin-biotinperoxidase method (Universal Kit).…”
Section: Electronic Microscopymentioning
confidence: 99%